2011
DOI: 10.2147/ijn.s14881
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular application of polyhedral oligomeric silsesquioxane nanomaterials: a glimpse into prospective horizons

Abstract: Revolutionary advances in nanotechnology propose novel materials with superior properties for biomedical application. One of the most promising nanomaterials for biomedical application is polyhedral oligomeric silsesquioxane (POSS), an amazing nanocage consisting of an inner inorganic framework of silicon and oxygen atoms and an outer shell of organic groups. The unique properties of this nanoparticle has led to the development of a wide range of nanostructured copolymers with significantly enhanced properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The biomedical applications of POSS arise from the materials biocompatibility, biostability nontoxicity, cytocompatibility, and resistance to degradation [9193]. It is due to these properties that POSS has been incorporated into wide range of nanostructured copolymers for a number of biomedical applications such as biomedical devices (heart valves, coronary stents) [94, 95], drug delivery [96], and tissue engineering [92]. …”
Section: Construction Of a Tissue Scaffoldmentioning
confidence: 99%
“…The biomedical applications of POSS arise from the materials biocompatibility, biostability nontoxicity, cytocompatibility, and resistance to degradation [9193]. It is due to these properties that POSS has been incorporated into wide range of nanostructured copolymers for a number of biomedical applications such as biomedical devices (heart valves, coronary stents) [94, 95], drug delivery [96], and tissue engineering [92]. …”
Section: Construction Of a Tissue Scaffoldmentioning
confidence: 99%
“…While being viscoelastic, polyhedral-oligomeric-silsesquioxane-poly(carbonate-urea)urethane (POSS-PCU) has been shown to have strength similar to natural arteries. POSS-nanocomposite polymer, used for cardiovascular implants, which include vascular bypass grafts, stents, and heart valves has been proved to have antithrombogenic properties [ 29 ].…”
Section: Surface Modification Of Blood Contacting Materialsmentioning
confidence: 99%
“…Studies have shown that the incorporation of POSS molecules into various polymers can influence their thermal stability and degradation behaviour at elevated temperatures, change the glass transition temperature, increase the resistance to composite oxidation, and improve mechanical strength [ 22 , 25 , 26 , 27 ]. Among different POSS-containing polymer materials, hybrid PU-POSS elastomers of various architectures have been widely studied in the literature [ 17 , 18 , 19 , 28 , 29 , 30 , 31 ], but PU foam chemically reinforced by POSS constitutes a new class of materials.…”
Section: Introductionmentioning
confidence: 99%